“Meat to be Delivered” : Disgust and Empathy in "Blonde" across Media (Comparatismi, 2023)
The article examines the role played by readers’ engagement with characters in their interpretive strategies of physical and moral disgust, by taking as its point of departure the concept of “character-centered illusion” developed by Marco Caracciolo. Through my case studies – the novel Blonde (2000) and its film adaptation (2022) – I attempt to show how formally and thematically similar works may produce a different reception of disgust, depending on a different structural juxtaposition between empathetic perspective-taking and cognitive dissonance toward their protagonist, Norma Jeane. In my comparative analysis I focus on a range of formal and thematic strategies adopted by the two works to elicit disgust in their recipients, distinguishing between differential and medium-specific techniques. I then examine how the two works foreground Norma Jeane’s fractured identity and altered state of consciousness as a means of problematizing readers’ engagement with her. While highlighting the continuities between the novel and the movie, I suggest that the latter disrupts the effective balance between empathy and cognitive dissonance of the former by relying heavily on the conventions of the psychological horror and Norma Jeane’s hallucinatory and delusional states, thus forcing a switch in viewers’ interpretive strategies.